Association of arbuscular mycorrhizal fungi in some angiospermic plants of Maharashtra, India - Sarwade, Prakash P; Kanade, M B; Ambuse, M G; Bhale, U N (International Multidisciplinary Research Journal, 2012)
The result showed that all the seven angiospermicÂ plants viz. Morinda citrifolia L., Carica papaya L., Lowsonia inermis L, Mimosa pudica L., Tamarandus indica L., Bauhinia recemosa Lamk andÂ Indigofera duthiei Drum. had AM fungal association in the roots and spore population in the rhizosphere soil. However, maximum percent root colonization of AM fungi was observed in Carica papaya (80 %) followed by others, while minimum in Lowsonia inermis (20%). Mimosa pudica (305) showed more spore density whereas less in Morinda citrifolia (59). Total four AMF was identified up to species level in which Glomus spp were found dominate followed by Acaulospora spp., Sclerocystis spp and Entrophosphora spp were found poorly distributed.